Deteksi Radar Terhadap Multi-Object Bergerak Dengan Pemrosesan Doppler - Abdullah, Reyhan Fahmirakhman; Arseno, Dharu; Suratman, Fiky Yosef (Proceedings Series on Physical & Formal Sciences, 2021)
In general, Radar or Radio Detection and Ranging is an electromagnetic wave system that is useful to measure distance and answer and make maps of surrounding objects. Radar has an advantage compared to other navigation tools, which is that radar does not require a transmitter station as a transmitter. Radar has an electronic wave emission principle that emits short radio wave pulses emitted in a narrow beam by a directional antenna. In this study, a multi-object radar detection simulation was carried out using Dopler processing both MTI and PDP, which later on the radar will detect related objects. Multi-object here is a condition that is achieved when a navigation radar detects more than one object. The result of this research is a multi-object detection process using the MTI and PDP methods and the matched-filter obtained from the predetermined data. So Doppler processing aims to mitigate the clutter signal to improve the detection performance of moving targets even though there is a dominance of signals originating from stationary clutter.